DETERMINANTS OF PURCHASE DECISION THROUGH CONSUMER TRUST IN SELECTING TOPICAL HALAL COSMETIC PRODUCTS - Yulianingsih Yulianingsih; Nandan Limakrisna; Hari Muharam (Yayasan Education and Social Center, 2023)
The study aimed to investigate the factors of religiosity, the function of the halal label, and product quality related to consumer confidence in selecting halal topical cosmetic products. The research subjects were female students at three Islamic-based universities in Bogor: the Tazkia Islamic Institute, Djuanda University, and Ibn Khaldun University. The total sample is 368 female students based on proportionate stratified random sampling. Data collection was carried out through questionnaires. This type of study includes Descriptive and verification research a procedure for analyzing the data using SEM Listrel. The results of this study indicate that 1) religiosity, the role of the halal label, and product quality have a positive and significant effect on consumer confidence; 2) religiosity, the role of the halal label, product quality, and consumer trust have a positive and significant effect on purchasing decisions; and 3) consumer trust is proven to be able to mediate the influence of religiosity, the role of halal labels, and product quality on purchasing decisions on halal topical cosmetics